Semi-automatic prostatic artery detection using cone-beam CT during prostatic arterial embolization. (August 2020) - Schnapauff, Dirk; Maxeiner, Andreas; Wieners, Gero; Denecke, Timm; Hamm, Bernd; Gebauer, Bernhard; Jonczyk, Martin
Background: Due to the broad variability of the prostatic artery (PA), its origin, small calibers, and tortuous courses, prostatic arterial embolization (PAE) is challenging, time-consuming, and results in high radiation doses. Purpose: To evaluate the accuracy of PA detection using cone-beam computed tomography (CBCT) performed from the aortic bifurcation in combination with a semi-automatic detection software in comparison to oblique view digital subtraction angiography (DSA) with internal iliac artery (IIA) injection. Material and Methods: Twenty-two consecutive patients were included in this retrospective, IRB-approved study between July and December 2017. CBCT from the aorta and 30° oblique-view DSA from both IIAs were obtained for PA detection. Results of suggested PAs from the semi-automatic vessel detection software after CBCT and IIA DSA were compared. Moreover, dose area product (DAP) was recorded. Statistical analysis included Spearman's correlation, Mann–Whitney U test, and the Wilcoxon test considering P <0.05 as significant. Results: PA type was classified significantly better with CBCT compared to DSA ( P =0.047). In IIA DSA, PAs could not be identified in 18% on the left and in 17% on the right side. CBCT detected all PAs, although truncation occurred in 59% because of the limited field of view. Mean DAP of the whole procedure was 257, 161.32±127, 909.36 mGy*cm 2 . Mean DAPs were for a single DSA 14, 502.51±9, 437.67 mGy*cm 2 and for one CBCT 15, 589.23±2, 722.49 mGy*cm 2 . A mean of 14.82 DSAs and only one CBCT were performed. CBCT accounted for 6% and DSA for 84% of the entire DAP of the procedure. Conclusion: CBCT with semi-automatic feeding vessel detection software detects PAs more accurately than IIA DSA and may reduce radiation dose.